2018
DOI: 10.1021/acs.jafc.8b03177
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Exposure and Development of Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the prevalent liver disease resulting from metabolic disorder, which is highly associated with obesity and type 2 diabetes. Emerging evidence has shown that insecticide exposure disrupts lipid and glucose metabolism and results in obesity and type 2 diabetes. However, the potential impact of insecticide exposure on the liver functions related to NAFLD development is largely unknown. Thus, this perspective focused on the current knowledge of the effect of insecticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…This pesticide is commonly used in agricultural and household [4,5]. In 2012, there was at least over 1 billion pound of pesticides usage in worldwide and it has dramatically increased for the last two decades [6,7]. Due to the widespread use of this chemical substance in agricultural and household, its residues in food may be harmful to non-targeting organisms, especially humans [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pesticide is commonly used in agricultural and household [4,5]. In 2012, there was at least over 1 billion pound of pesticides usage in worldwide and it has dramatically increased for the last two decades [6,7]. Due to the widespread use of this chemical substance in agricultural and household, its residues in food may be harmful to non-targeting organisms, especially humans [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Carbofuran contamination has caused many negative effects on organism such as an oxidative stress and impairment on motoric, cognitive, and memory functions [3,10]. Some studies have also proven that carbofuran effects are significantly harmful on the liver functions, especially result in the Non-Alcoholic Fatty Liver Disease (NAFLD) [7,11]. The dysfunction of the liver has become a serious illness in human considering that the liver is one of the important organs.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent but also non-persistent pesticides currently in use may also support the development of metabolic diseases [125,[131][132][133][134]. Experimental studies have allowed identification of the type of pesticides that promote fatty liver disease or changes in global metabolic homeostasis in animal models [123], such as organophosphorus or neonicotinoid or pyrethroid insecticides [135][136][137][138][139][140][141][142][143][144][145][146], triazine herbicides [147,148], glyphosate herbicides [149][150][151][152][153], or other families [154,155] and fungicides [152,[156][157][158][159][160][161] (Table 1).…”
mentioning
confidence: 99%
“…Pesticides alter glucose metabolism through the activation of glucose uptake, glycogenolysis, gluconeogenesis (for insecticides, see [136]; for diazinon or monocrotophos-treated animals, see [181][182][183], or inhibition of the mitochondrial respiratory chain [184]. They also have exerted effects through modulation of carbohydrate response element binding protein (Chrebp) gene expression levels [185] and changes in the expression of peroxisome proliferator-activated receptor (PPAR)β/δ and genes involved in glucose metabolism (FoxO1 and cAMP response element-binding protein, Creb) [186].…”
mentioning
confidence: 99%
“…Despite increasing concerns about pesticide residues in food products and water, various pesticides have been widely used to control plant diseases and improve crop yield. A previous study showed that insecticide exposure impaired lipid metabolism, thereby resulting in the development of NAFLD [21]. Moreover, recent studies have reported that fungicides such as propiconazole, flutriafol, cyproconazole, dazomet, fluazinam, hexaconazole, pyrasulfotole metabolite, and myclobutanil can cause NAFLD pathogenesis [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%